Phosphate minerals from the hydrothermal quartz veins in specialized S-type granites, Gemerska Poloma (Western Carpathians, Slovakia) - Stevko,M.; Uher,P.; Sejkora,J.; Malikova,R.; Skoda,R.; Vaculovic,T. (Journal of Geosciences, 2015)
An interesting association of phosphate minerals (fluorapatite, triplite, arrojadite-group minerals and viitaniemiite) was studied from intra-granitic hydrothermal quartz veins with minor amounts of albite, orthoclase, muscovite, fluorite, rhodochrosite, arsenopyrite, pyrite, bismuthinite and kobellite. The veins occur in highly evolved, Permian topaz-zinnwaldite leucogranite at the Elisabeth adit near Gemerska Poloma, Gemeric Unit, Western Carpathians (eastern Slovakia). Fluorapatite is enriched in Mn (˜4 wt. % MnO, 0.3 apfu Mn) and frequently replaced by triplite, representing the first known triplite occurrence in Western Carpathians. This mineral forms irregular aggregates (≤ 7 cm across), Mn/(Mn + Fe) atomic ratio of which attains 0.68 to 0.78 and F/(F + OH) = 0.89-0.92. “Fluorarrojadite-(BaNa)” to its Mn-dominant analogue “fluordickinsonite-(BaNa)” (both minerals still not approved by IMA-CNMNC) occurs as aggregates up to 2 cm across, showing Sr-rich (˜1.7 wt. % SrO, ˜0.36 apfu Sr) and Sr-poor (≤0.6 wt. % SrO, ≤0.13 apfu Sr) compositions with W site F/(F + OH) = 0.74-0.80 and M site Mn/(Mn + Fe) = 0.39-0.52. Rare viitaniemiite is Mn-rich (10 to 11 wt. % MnO, 0.34-0.38 apfu Mn). The phosphate mineralization in quartz represents a high-temperature hydrothermal assemblage. The F-rich Mn, Fe, Ca-bearing phosphates, fluorite, and muscovite precipitated most likely in presence of alkali- and fluorine-bearing post-magmatic fluids which altered primary magmatic minerals (especially Li-rich micas and alkali feldspars) and liberated some elements (Fe, Mn, Al, Ba, Sr, Na, K) from the adjacent granite.
Keywords: hydrothermal phosphates; triplite; arrojadite group; chemical composition; S-type granite; Slovak Republic